Sintering-free ceramsite for adsorbing fluorine ions in water and preparation method of sintering-free ceramsite

By using municipal sludge, fly ash and other wastes to prepare high-porosity sintered ceramates, and using chemical reactions between foaming agents and calcium chloride, the problem of poor fluoride ions adsorption in water by existing cerams is solved, and the problem of poor fluoride ions in water is achieved. It has efficient fluoride ion removal and waste resource utilization, reducing costs and energy consumption.

CN119191772APending Publication Date: 2024-12-27HUATIAN NANJING ENG & TECH CORP MCC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324238.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing sintered ceramides have poor effect in adsorbing fluoride ions in water, resulting in their failure to be widely used in sewage treatment.

Method used

Using municipal sludge, fly ash, cement and calcium chloride as raw materials, high porosity and high strength sintered ceramic granules are prepared through foaming and water spraying maintenance processes, and using foaming agents and calcium chloride The chemical reaction realizes the physical and chemical adsorption of fluoride ions.

Benefits of technology

The prepared sinter-free ceramite has high adsorption capacity, fast adsorption rate and good stability, with a fluorine ion removal efficiency of more than 85%, and at the same time, it realizes the resource utilization of waste, reducing production costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191772A_ABST
    Figure CN119191772A_ABST
Patent Text Reader

Abstract

The invention discloses sintering-free ceramsite for adsorbing fluorine ions in water and a preparation method of the sintering-free ceramsite, relates to the technical field of sewage treatment, and aims to solve the problem that the effect of adsorbing the fluorine ions in the water by the sintering-free ceramsite is not good enough. The method comprises the following steps: dewatering and drying the municipal sludge to a certain water content, crushing and sieving with a 200-mesh sieve; sieving the dried low-sodium fly ash to 200 meshes or below; the preparation method comprises the following steps: uniformly mixing pretreated municipal sludge and fly ash with cement and calcium chloride in proportion, adding a certain amount of water, fully and uniformly stirring to form a muddy raw material, adding a proper amount of a foaming agent, starting a foaming machine to foam the muddy raw material, and putting the foamed muddy raw material into a granulator for granulation; separating the granulated ceramsite from the granulator, curing at room temperature, spraying water to the surface of the ceramsite every day during curing, and obtaining the sintering-free ceramsite after water spraying curing is completed. The preparation process is simple and convenient, the cost is low, and the prepared ceramsite has high adsorption efficiency on fluorine ions in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sewage treatment, in particular to a sintering-free ceramsite for adsorbing fluoride ions in water and a preparation method thereof. Background Art

[0002] In the field of environmental science and water resources management, the treatment of fluoride ions has always been a topic of great concern. As an element widely present in nature, fluoride has both benefits and potential hazards to human health. Appropriate fluoride intake helps prevent tooth decay, but long-term excessive fluoride intake can lead to serious health problems such as fluorosis and fluorosis. Especially when the fluoride content in groundwater or surface water exceeds the standard, its impact on human health is particularly significant. Therefore, it is particularly important to develop efficient, economical and environmentally friendly fluoride ion removal technology.

[0003] The core of fluorine removal by adsorption lies in the selection and design of adsorption materials. Among many adsorption materials, ceramsite has gradually become a research hotspot in the field of adsorbents due to its excellent physical and chemical properties, good mechanical strength and environmental stability. The preparation of traditional ceramsite usually involves a high-temperature sintering process, which is not only energy-intensive but also may affect the adsorption performance of the material. Therefore, the development of a sinter-free ceramsite adsorbent not only retains the excellent properties of ceramsite, but also reduces the preparation cost, and has broad application prospects.

[0004] The preparation process of sinter-free ceramsite usually includes the steps of raw material screening, mixing, molding, and curing. First, a suitable raw material combination is selected based on the fluorine removal performance and cost considerations of the raw materials. Subsequently, the raw materials are mixed evenly in a certain proportion and made into ceramsite of the desired shape through molding processes such as pressing or extrusion. During the curing process, the physical and chemical effects between the raw materials are utilized to form a stable pore structure inside the ceramsite, thereby improving the adsorption performance. The entire preparation process does not require high-temperature sintering, thereby reducing energy consumption and costs.

[0005] The mechanism of fluoride ion adsorption in water by unsintered ceramsite mainly involves physical adsorption and chemical adsorption. Physical adsorption is the adsorption of fluoride ions on the surface of ceramsite through intermolecular forces such as van der Waals force; while chemical adsorption is the formation of stable chemical bonds through chemical reactions between surface functional groups and fluoride ions. In addition, the pore structure inside the ceramsite also plays an important role. It not only provides more adsorption sites for fluoride ions, but also promotes the diffusion and mass transfer process of adsorbates inside the ceramsite.

[0006] In addition, unsintered ceramsite also has good regeneration performance. After multiple adsorption-desorption cycles, its adsorption performance can still maintain a high level. This feature makes unsintered ceramsite have a wide range of application potential in drinking water treatment, industrial wastewater treatment and other fields.

[0007] However, the unsintered ceramsite currently on the market has not been widely used in the adsorption of fluoride ions in water. The main reason is that the existing methods have poor final effects. Therefore, there is an urgent need for an unsintered ceramsite for adsorbing fluoride ions in water and a preparation method thereof to solve this problem. Summary of the invention

[0008] The object of the present invention is to provide a sinter-free ceramsite for adsorbing fluoride ions in water and a preparation method thereof, so as to solve the problem that the effect of sinter-free ceramsite in adsorbing fluoride ions in water is not good enough.

[0009] To achieve the above object, the present invention provides the following technical solution: a method for preparing sinter-free ceramsite for adsorbing fluoride ions in water, comprising the following steps:

[0010] S1 Raw material pretreatment: dehydrate the municipal sludge to a certain moisture content, crush it and pass it through a 200-mesh sieve; sieve the dried low-sodium fly ash to less than 200 mesh;

[0011] S2 granulation: Mix the pre-treated municipal sludge and fly ash with cement and calcium chloride in proportion, add a certain amount of water and stir thoroughly to form a muddy raw material, add an appropriate amount of foaming agent, turn on the foaming machine to foam the muddy raw material, and then put it into the granulator for granulation;

[0012] S3 water spray curing: the granulated expanded clay is separated from the granulator and cured at room temperature. During the curing period, water is sprayed on the surface of the expanded clay every day. After the water spray curing is completed, the sintering-free expanded clay is obtained.

[0013] Preferably, the dehydration and drying temperature in step S1 is 110-115° C., the dehydration and drying time is 1-5 hours, and the moisture content of the municipal sludge after drying is 20±5%.

[0014] Preferably, in step S2, the raw materials include 30-40% municipal sludge, 10-15% fly ash, 30-40% cement, and 20-30% calcium chloride in terms of mass percentage, and the water added during stirring is 30% of the total weight of the raw materials.

[0015] Preferably, in step S2, the foaming agent is an animal protein foaming agent, the dilution ratio is 1:30, and the added amount is 2% of the total weight of the raw materials.

[0016] Preferably, in step S3, watering is performed 2 to 3 times a day to keep the surface of the expanded clay from cracking, and the overall curing time is 7 to 10 days.

[0017] Another technical solution provided by the present invention is a sinter-free ceramsite for adsorbing fluoride ions in water, which is prepared by the above method.

[0018] Preferably, the sinter-free ceramsite is used to treat fluoride ions in polluted water.

[0019] Preferably, under the condition that the concentration of fluoride ions in the polluted water is 50 mg / L, the amount of ceramsite used is 1 to 3 g per 500 mL of polluted water, and the adsorption time is 5 to 12 hours.

[0020] Preferably, after adding ceramsite to the polluted water, it is first stirred at a rate of 300 r / min for 1 to 3 hours, and the remaining adsorption time is static. After treatment, the removal efficiency of fluoride ions can exceed 85%.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The unsintered ceramsite for adsorbing fluoride ions in water and its preparation method have simple process and low cost. By optimizing the raw material ratio and operation steps, the unsintered ceramsite with high adsorption capacity, fast adsorption rate and good stability is prepared. The prepared ceramsite has high adsorption efficiency for fluoride ions in water.

[0023] 2. The sinter-free ceramsite for adsorbing fluoride ions in water and its preparation method not only realize the disposal of municipal sludge, but also open up a new way to recycle solid waste fly ash, making waste into waste; the main raw materials used are all waste, the production cost is low, and it has high environmental and economic benefits.

[0024] 3. The sinter-free ceramsite for adsorbing fluoride ions in water and its preparation method use the hydration reaction of fly ash and cement as the granulation basis, do not use the traditional sintering technology, while maintaining the high strength of the filler, saving energy consumption.

[0025] 4. The sinter-free ceramsite for adsorbing fluoride ions in water and its preparation method adopt a foaming machine for foaming, which greatly improves the porosity and specific surface area of ​​the filler compared with general sinter-free materials, and improves the adsorption capacity of the filler.

[0026] 5. The sinter-free ceramsite for adsorbing fluoride ions in water and its preparation method are as follows: calcium chloride is added to the ingredients, which reacts chemically with fluoride ions to generate insoluble calcium fluoride precipitates, thereby removing fluoride ions in water, achieving the dual removal effects of physical adsorption and chemical reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 SEM characterization of the sinter-free ceramsite prepared in Example 1 of the present invention Figure 1 ;

[0028] Figure 2 SEM characterization of the sinter-free ceramsite prepared in Example 1 of the present invention Figure 2 . DETAILED DESCRIPTION

[0029] A method for preparing sinter-free ceramsite for adsorbing fluoride ions in water comprises the following steps:

[0030] S1 Raw material pretreatment: Dehydrate the municipal sludge to a certain moisture content, crush it and pass it through a 200-mesh sieve; sieve the dry low-sodium fly ash (ash produced by burning magnesia coal, with a low sodium content, usually less than 2%, which can be widely used as a filler in the manufacture of refractory materials, ceramics, cement and other products) to less than 200 mesh;

[0031] S2 granulation: Mix the pre-treated municipal sludge and fly ash with cement and calcium chloride in proportion, add a certain amount of water and stir thoroughly to form a muddy raw material, add an appropriate amount of foaming agent, turn on the foaming machine to foam the muddy raw material, and then put it into the granulator for granulation;

[0032] Fly ash is water-hardening. The free silica and alumina in fly ash can show hydration and hardening ability when they are "stimulated" by alkaline substances. The combination with cement makes fly ash show excellent hydration performance in the later stage of curing, which can not only improve the strength of unfired expanded clay, but also improve the internal structure of unfired expanded clay and improve its freeze-thaw resistance.

[0033] Using a foaming agent to foam the mud raw material can produce a large number of tiny bubble structures in the mud raw material, further improving the porosity and specific surface area of ​​the unfired expanded clay, which is beneficial to improving the adsorption capacity of fluoride ion pollutants.

[0034] Calcium chloride is added to the ingredients, which reacts with fluoride ions (F - ) to produce insoluble calcium fluoride (CaF2) precipitation, thereby removing fluoride ions from water. This mechanism is based on the calcium ion (Ca 2+ ) can combine with fluoride ions to form water-insoluble compounds, thereby achieving the separation and removal of fluoride ions, so that the sinter-free ceramsite can remove fluoride ions to achieve the dual removal effects of physical adsorption and chemical reaction.

[0035] S3 water spray curing: the granulated expanded clay is separated from the granulator and cured at room temperature. During the curing period, water is sprayed on the surface of the expanded clay every day. After the water spray curing is completed, the sintering-free expanded clay is obtained.

[0036] The dehydration and drying temperature in step S1 is 110-115° C., the dehydration and drying time is 1-5 hours, and the moisture content of the municipal sludge after drying is 20±5%.

[0037] In step S2, the raw materials include 30-40% municipal sludge, 10-15% fly ash, 30-40% cement, and 20-30% calcium chloride in terms of mass percentage, and the water added during the mixing is 30% of the total weight of the raw materials.

[0038] In step S2, the foaming agent is an animal protein foaming agent, the dilution ratio is 1:30, and the added amount is 2% of the total weight of the raw materials. The use of animal protein foaming agent can make the unburned expanded clay carry a large amount of carbon source, so that the unburned filler can provide a carbon source for the growth of microorganisms when it is used as a wetland filler for biofilm formation, greatly shortening the biofilm formation time and improving the biofilm formation efficiency, so as to achieve the ability to remove nitrogen and phosphorus pollutants.

[0039] In step S3, watering is performed 2 to 3 times a day to keep the surface of the ceramsite from cracking, and the overall curing time is 7 to 10 days. After the curing is completed, the sinter-free ceramsite is obtained. It can be used to treat fluoride ions in polluted water.

[0040] For example: under the condition that the concentration of fluoride ions in the polluted water is 50 mg / L, if 0.5-3 g, preferably 1-3 g, of ceramsite is added to 500 mL of polluted water, and adsorption is carried out for 5-12 hours; for reference, after adding ceramsite to the polluted water, stir it at a rate of 300 r / min for 1-3 hours, and let it stand for the remaining adsorption time. The fluoride ion removal efficiency after treatment can exceed 85% under optimal conditions.

[0041] The following examples illustrate the preparation process of sinter-free ceramsite and the properties of the sinter-free ceramsite. In the following examples, municipal sludge was taken from the sludge in the dewatering room of the Jiangxinzhou Sewage Treatment Plant in Nanjing. The chemical composition of the municipal sludge is as follows: SiO2 25.64%, Al2O3 12.32%, Fe2O3 8.76%, CaO 9.57%, MgO 7.43%, K2O 1.66%, and Na2O 0.21%. The low-sodium fly ash is taken from the secondary fly ash produced by a power plant in Jiangnan. The main chemical components are as follows: SiO2 37.57%, Al2O3 32.53%, Fe2O3 11.29%, CaO 8.08%, MgO 2.11%; it is worth noting that the substances required in municipal sludge and low-sodium fly ash are mainly silicon dioxide and aluminum oxide, and the specific content has little effect on the adsorption of fluoride ions, and mainly affects the strength of expanded clay. Therefore, the specific sources of the above two raw materials will not have a significant impact on the following fluoride removal performance.

[0042] Embodiment 1:

[0043] During implementation, the municipal sludge is dehydrated and dried in an oven at 110℃~115℃ until the moisture content is about 20%, crushed and sieved through a 200-mesh sieve; the dried low-sodium fly ash is sieved to below 200 mesh. Weigh 350g of municipal sludge, 150g of fly ash, 350g of cement, and 150g of calcium chloride respectively, mix them evenly, add 300g of water by weight of the materials, stir them thoroughly, turn on the foaming machine to foam the muddy raw material, and after foaming, put the muddy raw material into the disc granulator for granulation, separate the granulated ceramsite from the disc granulator, and cure it at room temperature. During the curing period, sprinkle water on the surface of the ceramsite 2 to 3 times a day. After 7 to 10 days of water spraying and curing, the sintering-free ceramsite is obtained. According to the test, its specific surface area is 13.9m 2 / g, porosity of 54.71%, compressive strength of 4.78Mpa, particle size of 3-5mm. In the adsorption process, 0.5g of the prepared sinter-free ceramsite was first placed in a 500mL beaker, and then 500mL of 50mg / L sodium fluoride aqueous solution was added to the beaker, and the adsorption temperature was controlled at 25°C. The beaker was placed in a constant temperature magnetic stirrer, the speed was controlled at 300r / min, stirred for 1h, and sampled after standing for 4h. The adsorption result showed that the removal efficiency of fluoride ions in water was 74.55%.

[0044] Embodiment 2:

[0045] During implementation, the municipal sludge is dehydrated and dried in an oven at 110℃~115℃ until the moisture content is about 20%, crushed and sieved through a 200-mesh sieve; the dried low-sodium fly ash is sieved to below 200 mesh. Weigh 350g of municipal sludge, 150g of fly ash, 350g of cement, and 150g of calcium chloride respectively, mix them evenly, add 300g of water by weight of the materials, stir them thoroughly, turn on the foaming machine to foam the muddy raw material, and after foaming, put the muddy raw material into the disc granulator for granulation, separate the granulated ceramsite from the disc granulator, and cure it at room temperature. During the curing period, sprinkle water on the surface of the ceramsite 2 to 3 times a day. After 7 to 10 days of water spraying and curing, the sintering-free ceramsite is obtained. According to the test, its specific surface area is 13.9m 2 / g, porosity of 54.71%, compressive strength of 4.78Mpa, particle size of 3-5mm. In the adsorption process, 1g of the prepared sinter-free ceramsite was placed in a 500mL beaker, and then 500mL of 50mg / L sodium fluoride aqueous solution was added to the beaker, and the adsorption temperature was controlled at 25°C. The beaker was placed in a constant temperature magnetic stirrer, the speed was controlled at 300r / min, stirred for 1h, and sampled after standing for 4h. The adsorption result showed that the removal efficiency of fluoride ions in water was 80.60%.

[0046] Embodiment 3:

[0047] During implementation, the municipal sludge is dehydrated and dried in an oven at 110℃~115℃ until the moisture content is about 20%, crushed and sieved through a 200-mesh sieve; the dried low-sodium fly ash is sieved to below 200 mesh. Weigh 350g of municipal sludge, 150g of fly ash, 350g of cement, and 150g of calcium chloride respectively, mix them evenly, add 300g of water by weight of the materials, stir them thoroughly, turn on the foaming machine to foam the muddy raw material, and after foaming, put the muddy raw material into the disc granulator for granulation, separate the granulated ceramsite from the disc granulator, and cure it at room temperature. During the curing period, sprinkle water on the surface of the ceramsite 2 to 3 times a day. After 7 to 10 days of water spraying and curing, the sintering-free ceramsite is obtained. According to the test, its specific surface area is 13.9m 2 / g, porosity of 54.71%, compressive strength of 4.78Mpa, particle size of 3-5mm. In the adsorption process, 2g of the prepared sinter-free ceramsite was first placed in a 500mL beaker, and then 500mL of 50mg / L sodium fluoride aqueous solution was added to the beaker, and the adsorption temperature was controlled at 25°C. The beaker was placed in a constant temperature magnetic stirrer, the speed was controlled to 300r / min, stirred for 1h, and sampled after standing for 4h. The adsorption result showed that the removal efficiency of fluoride ions in water was 86.56%.

[0048] The above is only the result of adsorption of 0.5-2g of unsintered ceramsite for 5 hours. If 3g of unsintered ceramsite is used, the removal efficiency of fluoride ions in water can be stably achieved to be more than 85%.

[0049] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.

[0050] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A method for preparing sinter-free ceramsite for adsorbing fluoride ions in water, characterized in that: The specific steps include: S1 Raw material pretreatment: dehydrate the municipal sludge to a certain moisture content, crush it and pass it through a 200-mesh sieve; sieve the dried low-sodium fly ash to less than 200 mesh; S2 granulation: Mix the pre-treated municipal sludge and fly ash with cement and calcium chloride in proportion, add a certain amount of water and stir thoroughly to form a muddy raw material, add an appropriate amount of foaming agent, turn on the foaming machine to foam the muddy raw material, and then put it into the granulator for granulation; S3 water spray curing: the granulated expanded clay is separated from the granulator and cured at room temperature. During the curing period, water is sprayed on the surface of the expanded clay every day. After the water spray curing is completed, the sintering-free expanded clay is obtained.

2. The method for preparing a sinter-free ceramsite for adsorbing fluoride ions in water according to claim 1, characterized in that: The dehydration and drying temperature in step S1 is 110-115° C., the dehydration and drying time is 1-5 hours, and the moisture content of the municipal sludge after drying is 20±5%.

3. The method for preparing a sinter-free ceramsite for adsorbing fluoride ions in water according to claim 1, characterized in that: In step S2, the raw materials include 30-40% municipal sludge, 10-15% fly ash, 30-40% cement, and 20-30% calcium chloride in terms of mass percentage, and the water added during the mixing is 30% of the total weight of the raw materials.

4. The method for preparing a sinter-free ceramsite for adsorbing fluoride ions in water according to claim 3, characterized in that: In step S2, the foaming agent is an animal protein foaming agent, the dilution ratio is 1:30, and the added amount is 2% of the total weight of the raw materials.

5. The method for preparing a sinter-free ceramsite for adsorbing fluoride ions in water according to claim 1, characterized in that: In step S3, watering is performed 2 to 3 times a day to keep the surface of the ceramsite from cracking, and the overall curing time is 7 to 10 days.

6. A sinter-free ceramsite for adsorbing fluoride ions in water, characterized in that: The method is prepared by any one of claims 1 to 5.

7. The sinter-free ceramsite for adsorbing fluoride ions in water according to claim 6, characterized in that: The sinter-free ceramsite is used for treating fluoride ions in polluted water.

8. The sinter-free ceramsite for adsorbing fluoride ions in water according to claim 7, characterized in that: Under the condition that the concentration of fluoride ions in the polluted water is 50 mg / L, the amount of ceramsite used is 1 to 3 g for 500 mL of the polluted water, and the adsorption time is 5 to 12 hours.

9. The sinter-free ceramsite for adsorbing fluoride ions in water according to claim 8, characterized in that: After ceramsite is added to the polluted water, it is first stirred at a rate of 300 r / min for 1 to 3 hours, and the remaining adsorption time is static. After the treatment, the removal efficiency of fluoride ions can exceed 85%.